Toxicological evaluation of a novel cooling compound: 2-(4-methylphenoxy)-N-(1H-pyrazol-3-yl)-N-(2-thienylmethyl)acetamide. (2015) - Karanewsky, Donald S.; Arthur, Amy J.; Liu, Hanghui; Chi, Bert; Markison, Stacy
Abstract: A toxicological evaluation of a novel cooling agent, 2-(4-methylphenoxy)- N -(1 H -pyrazol-3-yl)- N -(2-thienylmethyl) acetamide (S2227; CAS 1374760-95-8), was completed for the purpose of assessing its safety for use in food and beverage applications. S2227 undergoes rapid oxidative metabolism in vitro, and in rat and dog pharmacokinetic studies is rapidly converted to its component carboxylic acid and secondary amine. S2227 was not found to be mutagenic or clastogenic in vitro, and did not induce micronuclei in polychromatic erythrocytes in vivo . The secondary amine hydrolysis product, N -(2-thienylmethyl)-1 H -pyrazol-3-amine (M179), was also evaluated for genotoxicity. In subchronic oral toxicity studies in rats, the no-observed-adverse-effect-level (NOAEL) for S2227 was 100 mg/kg/day (highest dose tested) when administered by oral gavage for 90 consecutive days. Furthermore, S2227 demonstrated a lack of maternal toxicity, as well as adverse effects on fetal morphology at the highest dose tested, providing a NOAEL of 1000 mg/kg/day for both maternal toxicity and embryo/fetal development when administered orally during gestation to pregnant rats.